Design and fabrication of solar box cooker / Muhammad Shahir Ismail - Ismail, Muhammad Shahir (2022)
Mechanical engineering students in semester 5 were tasked with developing a product that helps in the solving of a common problem. The fundamental concept is to solve a widespread problem, which is using clean, renewable, and readily available solar energy as fuel. The goal of this project is to design and build a working solar cooker and apply thermal energy storage. The proposal outlines the primary phases in manufacturing a product, which include doing research, conducting a literature study, creating a concept design to be visualised in 3D rendering software, and fabricating the product. As a consequence of the completion of this proposal, the ability to build a good proposal for manufacturing an engineering design should improve, which will help in the future professional environment of the engineering world.